Complex field verification using a large area CMOS MAPS upstream in radiotherapy. (1st August 2022) - Pritchard, J.L.; Velthuis, J.J.; Beck, L.; Li, Y.; De Sio, C.; Ballisat, L.; Duan, J.; Shi, Y.; Hugtenburg, R.P.
Abstract: A multileaf collimator (MLC) is an integral component in modern radiotherapy machines as it dynamically shapes the photon field used for patient treatment. Currently, the MLC leaves which collimate the treatment field are mechanically calibrated to ±1 mm every 3 months and during pre-treatment calibration are calibrated to the mechanically set leaf positions. Leaf drift can occur between calibration dates and hence exceed the ±1 mm tolerance. Pre-treatment verification, increases LINAC usage time so is seldom performed for each individual patient treatment, but instead for an acceptable sample of patients and/or treatment fractions. Independent real-time treatment verification is therefore desirable. We are developing a large area CMOS MAPS upstream of the patient to monitor MLC leaf positions for real-time treatment verification. CMOS MAPS are radiation hard for photon and electron irradiation, have high readout speeds and low attenuation which makes them an ideal upstream radiation detector for radiotherapy. Previously, we reported on leaf position reconstruction for single leaves using the Lassena, a 12 × 14 cm 2, three side buttable MAPS suitable for clinical deployment. Sobel operator based methods were used for edge reconstruction. It was shown that the correspondence between reconstructed and set leaf position was excellent and resolutions ranged between 60.6 ± 8 and 109 ± 12 μm for a single central leaf with leaf extensions ranging from 1 to 35 mm using 0.3 sec of treatment beam time at 400 MU/min. Here, we report on leaf edge reconstruction using updated methods for complex leaf configurations, as occur in clinical use. Results show that leaf positions can be reconstructed with resolutions of 62 ± 6 μm for single leaves and 86 ± 16 μm for adjacent leaves at the isocenter using 0.15 sec at 400 MU/min of treatment beam. These resolutions are significantly better than current calibration standards.